The power of the Agile business analyst : 30 surprising ways a business analyst can add value to your Agile development team - Cooke, Jamie Lynn (IT Governance Publishing, 2018)
Drawing on her extensive experience, Jamie proposes a new role for Agile projects: The Agile business analyst. She details 30 achievable ways that such a role will increase relevance, quality and overall business value, and provide business users with crucial support.